Etika dan Akhlak Dalam Bisnis Islam - Sufiani Zahra; A. Anggie Zabrina Arief; Muh. Afta Noer; Aulia Ananda Putri; Supriadi (STIS DAFA MATARAM, 2022)
This study aims to explore a profound understanding of Business Ethics in the context of Islam, focusing on the moral values and ethics outlined in the Quran and Hadith. The method employed includes the analysis of Islamic religious texts and relevant literature discussing economic and business concepts from an Islamic perspective. The findings of this study indicate that Islamic business ethics entail not only compliance with legal rules or avoidance of unethical behavior, but more deeply, grounding business activities in moral values such as honesty, justice, and social responsibility. A key contribution of this research is providing a better understanding of how Islamic business ethics can serve as a guide for business practitioners to foster positive relationships with society and promote sustainable development within the framework of a global economy.